2011
DOI: 10.5530/pj.2011.20.10
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro studies on the antioxidant assay profiling of Withania somnifera L. (Ashwagandha) Dunal root: Part 1

Abstract: a b s t r a c tWithania somnifera Dunal, commonly known as ashwagandha, has been used for centuries in ayurvedic medicine to increase longevity and vitality. Various groups of researchers support its polypharmaceutical uses by confirming anti-inflammatory, immuno-modulatory and antistress properties in the whole plant extract. The present investigation adds up the antioxidant assay profiling in this list. The Ashwagandha root extracts were prepared in different solvents of varied polarity in a sequential fashi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 38 publications
6
12
0
Order By: Relevance
“…Amongst solvents the mean value of total flavonoids content (mg CE/g) in ethanolic extracts (1.16) was higher than aqueous extracts (0.82). Our finding is in agreement with previous investigation which reported 0.38 mg/g flavonoids content in water extracts of ashwagandha roots [12]. Total flavonoids content ranged from 2.87 to 4.98 mg/g d.w.b.…”
Section: Resultssupporting
confidence: 93%
“…Amongst solvents the mean value of total flavonoids content (mg CE/g) in ethanolic extracts (1.16) was higher than aqueous extracts (0.82). Our finding is in agreement with previous investigation which reported 0.38 mg/g flavonoids content in water extracts of ashwagandha roots [12]. Total flavonoids content ranged from 2.87 to 4.98 mg/g d.w.b.…”
Section: Resultssupporting
confidence: 93%
“…In present work, this assay was used to determine the effect of ARE on DNA damage in selected lymphocyte exposed to H 2 O 2 and protection of DNA damage by ARE clearly indicates its prophylactic potential at molecular level. As proved earlier by us, 13,14 ARE exhibited a scavenging effect on H 2 O 2 which might have contributed to inhibition of DNA damage in rat lymphocytes. Our results corroborate with previous work where Aherne and O'Brien showed that pre-treatment with quercetin and rutin had reduced DNA damage induced in Caco-2 and Hep G2 cells by a subsequent exposure to H 2 O 2 .…”
Section: Discussionsupporting
confidence: 69%
“…30 The novel herbomineral test formulation based on Ashwagandha might act as an effective anti-inflammatory and immunomodulatory product, and this can be used as a complementary and alternative treatment for the prevention of various types of inflammatory and auto-immune disorders. 31 In continuation with our previous work 13, 14 we have examined ex-vivo model of stressed rat lymphocytes and observed AChE inhibitory and pro-antioxidant activities of ARE. According to Atta-ur-Rahman and Choudhary, 32 the use of antioxidants may slow the progression of Alzheimer's disease (AD) and minimize neuronal degeneration.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations